Respostas
respondido por:
1
3s + 1g = 12 ( vezes - 1)
3s + 3g = 15
____________
-3s - 1g = -12
3s + 3g = 15
--------------------
// 2g = 3
g = 3/2 = 1,5 ****
3s + 1 ( 1,5) = 12
3s + 1,5 = 12
3s = 12 - 1.5
3s = 10.5
s = 10.5/3 =3,5 ***
3s + 3g = 15
____________
-3s - 1g = -12
3s + 3g = 15
--------------------
// 2g = 3
g = 3/2 = 1,5 ****
3s + 1 ( 1,5) = 12
3s + 1,5 = 12
3s = 12 - 1.5
3s = 10.5
s = 10.5/3 =3,5 ***
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás